Advances in Metal Complex-Catalyzed Oxidation of Alkanes - Li, Chenhao; Zhang, Xiaoli (Scientific Journal of Technology, 2025)
With the development of green chemistry, metal complex-catalyzed oxidation of alkanes (linear and cyclic) has emerged as a key strategy for the efficient conversion of inert C(sp³)–H bonds. This review summarizes recent advances in the selective oxidation of alkanes under mild conditions using metal complexes (e.g., Cu, Fe, Co, Ni), with a focus on ligand design and its regulatory effects on catalytic activity and selectivity. These systems employ radical or metal-oxo intermediate pathways, utilizing green oxidants such as H₂O₂ or O₂, significantly reducing energy consumption and byproduct formation. The study provides an efficient and sustainable catalytic approach for the valorization of petroleum resources (e.g., nylon monomer synthesis), contributing to the advancement of green chemical engineering. Future research should further optimize catalyst stability and recyclability while exploring biomimetic and multimetallic cooperative catalytic systems.